2010
DOI: 10.1109/mc.2009.417
|View full text |Cite
|
Sign up to set email alerts
|

Puzzle-Based Learning for Engineering and Computer Science

Abstract: A number of universities are introducing courses, modules, or freshman seminars that relate to the puzzle-based learning paradigm. The purpose of such units is to attract, motivate and retain engineering/computer science students, and to increase their mathematical awareness and their problem-solving skills. This is essential in developing students as general problem-solvers, rather than training students to limit their thinking to the problems that are immediately pertinent to the specific area that they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…As Falkner et al [15] put it: "the ultimate goal of puzzlebased learning is to lay a foundation for students to be effective problem solvers in the real world".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Falkner et al [15] put it: "the ultimate goal of puzzlebased learning is to lay a foundation for students to be effective problem solvers in the real world".…”
Section: Discussionmentioning
confidence: 99%
“…There are good discussions of the relationships between the three concepts in [14,15] and between Problem-Based Learning and Puzzle-Based Learning in [3].…”
Section: Theoretical Considerations and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…As per Falkner et al (2010) [8], "The goal of puzzlebased learning is to lay a foundation for students to be effective problem solvers in the real world. At the highest level, problem-solving in the real-world calls into play three categories of skills: "dealing with the vagaries of uncertain and changing conditions; harnessing domainspecific knowledge and methods; and critical thinking and applying general problem-solving strategies."…”
Section: Puzzle Based Learningmentioning
confidence: 99%
“…In (Falkner et al 2010) and (Falkner et al 2011) we have identified goals for developing learning in a puzzle-based, domain-free, context, and presented Copyright c 2012 by University of Debrecen a plan for a course that developed puzzle-solving skills in a variety of contexts. To review the core points, puzzles were used in order to teach problem-solving, because:…”
Section: Introductionmentioning
confidence: 99%